Impact of High Energy Cosmic Rays on Global Atmospheric Electrical Parameters over Different Orographically Important Places of India. (19th June 2013) - Kumar, Adarsh; Singh, H. P.
Abstract : Global atmospheric electrical parameters such as atmospheric conductivity, air-earth current density, atmospheric electric field, and atmospheric potential have been calculated for eighty different orographically important places of India under the influence of cosmic ray modulation factor due to Forbush decrease assuming fair weather conditions. The results have been compared with the earlier work of Kumar et al. (1998) and show that the correlation between cosmic rays and global atmospheric electrical parameters near the earth surface depends upon the relative magnitudes of galactic cosmic ray particles.